Bi5O7I/g-C3N4 Heterostructures With Enhanced Visible-Light Photocatalytic Performance for Degradation of Tetracycline Hydrochloride - Yang, Yang; Lai, Min; Huang, Jialei; Li, Jinze; Gao, Ruijie; Zhao, Ziming; Song, Huatang; He, Jixiang; Ma, Yan (Frontiers in Chemistry, 2021)
Bi5O7I/g-C3N4 p-n junctioned photocatalysts were synthesized by alcohol-heating and calcination in air. The structures, morphologies and optical properties of as-prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV–Vis diffuse reflectance spectroscopy (DRS). Photocatalytic activity of the heterojunctioned composites were evaluated by degradation of Rhodamine B (RhB) and tetracycline hydrochloride (TCH) under visible light illumination. The results indicated that the composites exhibited superior efficiencies for RhB and photodegradation in comparison with pure BiOI, pure Bi5O7I and pure g-C3N4. An effective built-in electric field was formed by the interface between p-type Bi5O7I and n-type g-C3N4, which promoted the efficient separation of photoinduced electron-hole pairs. In addition, 8% Bi5O7I/g-C3N4 composite showed excellent photostability in a five-cycle photocatalytic experiment. Experiments on scavenging active intermediates revealed the roles of active species.